Hypopigmented Mycosis Fungoides: A Retrospective Study - Diya Katrina Koikkara; Sheethal K. Jose; Priya Sara Kuryan; Dincy Peter; Leni George; Gauri Dinesh Mahabal; Meera Thomas; Susanne Pulimood (Current Medical Issues)
Background: Hypopigmented mycosis fungoides (HMF) is a rare cutaneous T-cell lymphoma seen in children with persistent hypopigmented patches, histopathology showing epidermotropism of atypical lymphocytes, and immunohistochemistry being predominantly CD8+. Methodology: A cross-sectional retrospective study on patients with HMF between June 2009 and January 2024 at a tertiary care center in South India was done. The clinical profile of the patients, serology, and histopathology with immunohistochemistry were reviewed. Results: Of 34 patients included in the study, the mean age at presentation was 32.65 ± 13.25 years, duration of symptoms was 5.33 ± 0.83 years, and the mean age at onset was 27.29 ± 2.73 years. All but one patient had multiple patches, 18(53%) with both covered and photo-exposed sites and 14(41%) having only over covered sites. Nine patients presented with mixed morphology of lesions along with hypopigmented patches. Seventeen (50%) patients had more than 10% body surface area involved, none had systemic disease. Histopathology revealed epidermotropism (100%) and lymphocyte tagging (82%). Immunohistochemistry showed CD8 predominance in 56%. Of the patients with only hypopigmented lesions, 64% showed CD8+ predominance, and 67% of patients with mixed morphology had CD4+ predominance. Conclusions: HMF should be considered in patients with persistent hypopigmented patches predominantly over covered areas. Usually, HMF has an earlier age of onset, but our study had a mean age at onset of 27 years. Hypopigmented lesions were mostly CD8+ and mixed morphology of lesions were mostly CD4+ on immunohistochemistry.